f(x) = 2x + 4 and g(x) = -8f(x). = What equation shows the correct rule for the function g? O g(x) = -4x O g(x) = -4x + 4 = g(x) = -8x - 32 O g(x) = -4x - 32 – -
![fx 2x 4 and gx 8fx What equation shows the correct rule for the function g O gx 4x O gx 4x 4 gx 8x 32 O gx 4x 32 class=](https://us-static.z-dn.net/files/d15/dc01151f91c655bb94ca808846971245.png)
The given functions are
[tex]\begin{gathered} f(x)=\frac{1}{2}x+4 \\ g(x)=-8f(x) \end{gathered}[/tex]Multiply f by -8 to get g
[tex]\begin{gathered} g(x)=-8(\frac{1}{2}x+4) \\ g(x)=-8(\frac{1}{2}x)+(-8)(4) \\ g(x)=-4x+(-32) \\ g(x)=-4x-32 \end{gathered}[/tex]The correct answer is D